2021
DOI: 10.5604/01.3001.0015.5233
|View full text |Cite
|
Sign up to set email alerts
|

BBAP amplification profiles of apple varieties

Abstract: Several types of allergies are currently known and are characterized by an exaggerated response of the immune system to substances from various sources called allergens. One of them is a food allergy, which is becoming more common in the population. For this reason, it is necessary to describe the issue from several aspects including genomic variability of plant allergens. The objective of this study was to analyse intraspecific variability of Bet v 1 of 10 different varieties of apple species (Malus domestica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Plant allergens are typical with their great variability at the proteomic and genomic sequences and the multilevel analysis of these sequences is an actual part of research activities because of the raising number of food allergies worldwide. Previously, in silico approach was used for profilins and oleosins (Kyseľ et al, 2022) and the transfer of the in silico based predictions to an DNA marker techniques were applied for different plant species in the case of the analysis of Bet v 1 sequences as well as profilins (Speváková et al, 2021;Urbanová and Žiarovská, 2021;Kováčik et al, 2024).…”
Section: Resultsmentioning
confidence: 99%
“…Plant allergens are typical with their great variability at the proteomic and genomic sequences and the multilevel analysis of these sequences is an actual part of research activities because of the raising number of food allergies worldwide. Previously, in silico approach was used for profilins and oleosins (Kyseľ et al, 2022) and the transfer of the in silico based predictions to an DNA marker techniques were applied for different plant species in the case of the analysis of Bet v 1 sequences as well as profilins (Speváková et al, 2021;Urbanová and Žiarovská, 2021;Kováčik et al, 2024).…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that homologs of Bet v 1 found in several plants cause the so-called cross-reaction phenomenon in humans [10]. The variability of homologs of Bet v 1 with the BBAP technique used was monitored in Malus domestica [20] and in cereals, specifically in Avena Sativa [23]. In a study conducted by Žiarovská and co-authors, they performed an analysis where allergen Bet v 1 homologs were identified in a range of 30 plant species.…”
Section: Resultsmentioning
confidence: 99%
“…Forward primer was designed for a region of high homology in Malus domestica [18]. A degenerate primer has degeneracy situated at positions 12 (S) and 14 (K), meaning that position 12 can be occupied by either guanine or cytosine, and position 14 can be filled with either thymine or guanine [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, degenerate primers that anneal a variable and conserved part of PR-10 protein homologues genes in the BBAP technique were applied to analyse intraspecific variability of Malus domestica Borkh. cultivars (Speváková et al 2021). Amplicons were generated and formed relatively monomorphic profiles, indicating the stability of the given isoforms of Bet v 1 within the selected apple cultivars.…”
Section: Discussionmentioning
confidence: 98%